RESEARCH AND DEVELOPMENT OF DIAZEPAM SOLID DISPERSION POWDER USING NATURAL POLYMERS - Handa, Uditi; Saroha, Kamal (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of this study was to enhance the solubility and dissolution rate of a poorly water-soluble drug by solid dispersion (SD) technique, in order to conduct an investigation of the effect of these natural hydrophilic polymers on release mechanism from SD. Methods: The SD of diazepam (DZM) were prepared by using modified sodium alginate (SA) and modified guar gum (GG) in different drug: polymer ratios (1:1 and 1:2) by using physical mixture method (PM) and fusion method (FM). Further, the formulations were characterized for calibration curve, Fourier transforms infrared spectroscopy (FTIR) studies, % age practical yield, drug content estimation, solubility studies, dissolution studies. Results: The pure drug and SD were characterized by pre and post-formulations studies. The %age practical yield ranged from 92.9±0.25 to 49±0.57%, and the drug content estimation ranged from 99.34±0.40 to 65.25±0.25 %. The FTIR studies shown that the compatibility between pure drug and natural polymers was stable. All the SD showed improved solubility as compared to the pure drug (PD). SD prepared with modified SA (1:2) by PM and FM shown the huge enhancement of solubility and dissolution rate of the DZM. This can be specific to the improvement in wettability and dispersibility, as well as enhances the drug amorphous fraction. Conclusion: On the basis of the research study, the SD technique shows the enhancement in the solubility of poorly water-soluble drug using natural polymers. SD containing natural polymers prepared with PM and FM shown the remarkable improvement in the release outline compared with PD, DZM.